A dramatic approach to poetry, the poem Wait for Me at the Edge of the Sea by the poet Youssef Al-Sayegh as a model (Journal of the College of Basic Education, 2023)
The art of theater is one of the important human arts in any society and in various civilizations and eras to this day. Creators and those interested in theatrical arts have been using reality as well as life circumstances to write their theatrical texts, trying to address social problems and present their different points of view.Those interested in dramatic art and writers of literature did not suffice at this point in their treatment of life circumstances and problems, but rather opened up to other worlds of creativity represented by their use of fictional art. and poetry. Narrative art.